A Clinical Trial Investigating Telehealth and In-Person Social Communication Skills Training for People With Traumatic Brain Injury: Participant-Reported Communication Outcomes. Issue 4 (July 2020) - Rietdijk, Rachael; Power, Emma; Attard, Michelle; Heard, Robert; Togher, Leanne
Abstract : Objective: To investigate the efficacy of telehealth-based and in-person social communication skills training (TBIconneCT) for people with moderate to severe traumatic brain injury (TBI) based on outcomes reported by the survivor and a close communication partner. Setting: Australia. Two telehealth dyads were located outside Australia. Participants: Adults ( n = 51) at least 6 months after moderate-severe TBI with social communication skills deficits, and their usual communication partners (family members, friends, or paid carers). Design: Partially randomized controlled trial, with a telehealth intervention group, in-person intervention group, and a historical control group. Main Measures: La Trobe Communication Questionnaire (LCQ) (total score, and number of items with perceived positive change). Both self- and other-reports. Results: Trained participants had significantly more items with perceived positive change than did historical controls. A medium effect size in the sample was observed for improvements in total score reported by trained communication partners after treatment. Comparisons between telehealth and in-person groups found medium to large effect sizes in the sample, favoring the telehealth group on some LCQ variables. Conclusions: Whether delivered via telehealth or in-person, social communication skills training led to perceived positive change in communication skills. It was unexpected that outcomes for the telehealth group were better than for the in-person group on some variables. Abstract : Supplemental Digital Content is Available in the Text.